Execution of replication in heterogeneous database systems - Khadzhynov, W.; Maksymiuk, M. (Реєстрація, зберігання і обробка даних, 2006)
Database replication is a mechanism which allows distributed databases stay in synchronized and consistent state. In heterogeneous case there is a set of databases with different platforms, what additionally complicates this process. High demand for this technique causes that replication issue is developed very fast nowadays. Database replication mechanism consists in intercepting data modifications and propagating them to other databases where they are executed again. This process is very complex and there are many variants and types of replication. In this paper are discussed database replication classification (synchronous, asynchronous, multiple master, master slave), kinds of replication conflicts with resolving strategies, data modification capturing and publication-subscription model. There is introduced an example for realization of replication in heterogeneous environment. Also are discussed aspects of independence database assess mechanism from specific platform, what can be used in implementation of heterogeneous database replication. Предложено решение для реализации репликации в неоднородных средах баз данных при помощи моделей Master-Slave и Multiple master в синхронном и асинхронном режимах. Дана оценка возможным конфликтам и стратегии их преодоления, способам «перехвата» модификаций в базе. Рассмотрены применение схемы «публикатор–подписчик» и различные способы проведения модификаций в удаленных базах данных. Запропоновано рішення для реалізації реплікації у неоднорідних середовищах баз даних за допомогою моделей Master-Slave та Multiple master у синхронному й асинхронному режимах. Дано оцінку можливим конфліктам і стратегії їх подолання, засобам «перехоплення» модифікацій у базі. Розглянуто застосування схеми «публікатор–передплатник» і різні засоби проведення модифікацій у віддалених базах даних.